Implementasi Pendidikan Karakter dalam Membangun Kemandirian dan Disiplin Siswa di MTsN Kanigoro Kras Kab. Kediri - Santosa, Agus Dwi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This study tries to answer the following questions: 1) How is the implementation of character education in self-reliance and discipline to build students character in MTsN Kanigoro, Kras District, Kediri; 2) What factors that influence the implementation of character education in self reliance and discipline to build students character in MTsN Kanigoro Kras District. Kediri. This study uses a qualitative approach with case study method. The results reveal that character education is implemented through planning, integrated implementation through instruction, character building through self-development, while factors influencing the implementation are classified into two: internal and external factors.